2017
DOI: 10.1063/1.4979957
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra of 5-fluorouracil molecules isolated in inert Ar matrices, and their films on graphene oxide at 6 K

Abstract: The FTIR spectra of 5-fluorouracil (5FU) molecules isolated in low-temperature (T = 6 K) argon matrices were observed in the infrared range of 3800–200 cm−1. The FTIR spectra of graphene oxide (GO) films on a copper mirror at a temperature of 6 K and the spectra of 5FU films grown on GO films were recorded for the first time. Estimates of the 5FU tautomer population using quantum-mechanical methods DFT/B3LYP and MP2, and calculations of the 5FU vibrational spectra using the DFT/B3LYP/6-311++G(df,pd) method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…[ 34 ] The spectrum with frequencies less than 1000 cm −1 attributes the absorption bands of stretching vibrations of the pyrimidine ring and planar/nonplanar deformation vibrations of 5‐FU. [ 35,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] The spectrum with frequencies less than 1000 cm −1 attributes the absorption bands of stretching vibrations of the pyrimidine ring and planar/nonplanar deformation vibrations of 5‐FU. [ 35,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with earlier work on 5FU with four water molecules [ 23 ] and with experimental findings. [ 31,37,65 ] The authors also observed a difference between keto and enol forms with four water molecules of about 30 kJ/mol at the MP2/6‐31+G(d,p) level of theory. Early infrared (IR) studies in the Ar matrix revealed signals from the keto form of 5FU only, [ 37 ] and the potential concentration of minor tautomers was assumed to be below 0.1%.…”
Section: Resultsmentioning
confidence: 97%
“…Similar conclusion from low‐temperature IR matrix studies were reported recently. [ 65 ] In addition, recent photoluminescence studies also indicate the keto form as the most abundant form. [ 31 ] Thus, on the previously optimized structures of K_5w and K_5m complexes, we performed single‐point calculations, with the original B3LYP functional lacking a dispersion correction term.…”
Section: Resultsmentioning
confidence: 99%
“…Поэтому, изучение взаимодействия галогенпроизводных урацила с наночастицами представляет интерес для создания композитных наноструктур с различными биотехнологическими и биомедицинскими функциями. Исходя из опыта наших предыдущих исследований композитных пленок [9][10][11], в качестве объектов данного исследования были выбраны биокомпозитные пленки: 5BrU/GO, 5BrU/MoS 2 , 5BrdU/GO и 5BrdU/MoS 2 .…”
Section: спектральні і структурні особливості біокомпозитних плівок оunclassified